The Role of State Budget and Tax Policy in Economic Stability - Sherali qizi, Samadova Jasmina; Tillaoy, Rakhmonova (Journal of Innovation in Education and Social Research, 2025)
The state budget and tax policy serve as key instruments for maintaining economic stability and promoting sustainable development. Through effective fiscal policy, the government stimulates economic growth, supports infrastructure development, finances social programs, and ensures macroeconomic balance. Taxes, as the main source of budget revenue, play a crucial role in achieving both economic efficiency and social justice, particularly in the context of global economic changes and the post-pandemic recovery.